The sex profile of skeletal remains from a cemetery of Chinese indentured labourers in South Africa - Victoria Gibbon; Goran Štrkalj; Maria Paximadis; Paul Ruff; Clem Penny (South African Journal of Science)
For a short period of time in the early 20th century, indentured labourers from China were imported to work on the South African gold mines. The Raymond A. Dart Collection of Human Skeletons contains 36 skeletons sourced from a Chinese cemetery of this time period on the site of the old Witwatersrand Deep Gold Mine. An earlier morphometric study on this collection recorded a high number of female individuals. However, the general historical records from the early gold mining era conflict with the results of this study, stating that very few Chinese females were among those to arrive in South Africa. In this study, the sex profile of this collection was analysed using molecular sex identification through the amelogenin gene. Results were obtained for 13 (41.93%) specimens, all of which were determined to be male - data that correspond well with the historical records.